PENGARUH OPINI AUDIT GOING CONCERN TERHADAP PERGANTIAN KANTOR AKUNTAN PUBLIK SECARA SUKARELA DENGAN KARAKTERISTIK KOMITE AUDIT SEBAGAI VARIABEL PEMODERASI - Joviana, Theresia Monica; Pikir, Toto Warsoko; Oki, Ariston (Jurnal Akuntansi Kontemporer, 2015)
Going concern audit opinion is an audit opinion which is issued by independent auditor when auditor finds doubts about compa-ny’s business continuity. The issuance of going concern audit opinion will make managerial tend to change its audit firm volun-tary because they expect that appointed independent auditor will issue an unqualified opinion. Audit committee is a committee which is formed by board of commissioner to give recommendations about audit firm’s selection. Audit committees have a role to settle disputes between management and independent auditor when the auditor is not issue audit opinion which is expected by management. The role and characteristics of audit committee will be more likely to resist managerial attempts to change its audit firm voluntarily following the issuance of a going concern report. The study aims to (1) examine whether going concern audit opinion will affect management to changes its audit firm; (2) provide evidence that audit committee characteristics which are prox-ied by independent audit committee, have financial expertise, and audit committee activities is able to moderate the effect of going concern audit opinion on the change of audit firm voluntarily. This study use non-financial companies that listed on Stock Ex-change during the period 2003-2013 as sample. This study provides evidence that (1) going concern audit opinion does not signifi-cantly affect management to change its audit firm voluntarily; (2) the characteristics of audit committee is not able to moderate the effect of going concern audit opinion on the change of audit firm voluntarily.